Pengembangan Model Industry Kreatif melalui E-Commerce menjadi Wirausaha Kompetitif : Studi Kasus Pelaku Usaha Thrifting di kota Batam - Brigida Endah Nuraeni; Pilifus Junianto; Edi Sumarya; Oktavianus Darmin; Elisabeth Hilariana Pratiwi (Jurnal Minfo Polgan, 2026)
The aim of this research is to analyze in depth the use of e-commerce by thrifting businesses in Batam City. This study employed a qualitative approach with a case study design. The main findings indicate that Creative Industry Aspects (CIA) have a significant positive effect on e-commerce adoption (UoEf), and e-commerce adoption significantly improves industry players' competency (Compt). The indirect effect of CIA on Compt through UoEf is significant, although the direct effect of CIA on Compt is insignificant. This confirms the importance of digitalization mediation in transforming human resource quality in the garment/creative industry sector. The model shows that the explained endogenous variables are relatively moderate (R² ~0.40 for UoEf) and low (R² ~0.21 for Compt), indicating the presence of other factors outside the model that also influence e-commerce competency and adoption.